The Influence of Leadership Style and Work Engagement on Job Satisfaction and Its Impact on Nurse Performance in RSUD Dr. Abdul Aziz, City of Singkawang, West Kalimantan - Susanti, Peni; Suteja, Jaja (Transforma Jurnal Manajemen, 2023)
This study aims to determine and analyze the effect of transformational leadership and work culture on nurse performance mediated by job satisfaction at RSUD dr. Abdulaziz. The results of this study are expected to provide input for hospital leaders and nursing managers to use the results of this study to be taken into account in determining and providing appropriate interventions to improve the performance of nurses in providing nursing care services, especially in hospitals. The research method used is descriptive analysis and verification. The data collection used was interviews using a questionnaire accompanied by observation and literature techniques. The sample was taken using proportionate random sampling. Data collection in the field will be carried out in 2022. The data analysis technique uses Path Analysis. The results showed that in general transformational leadership, work culture, job satisfaction, and nurse performance tended to be less good. There is an influence of transformational leadership and work culture on job satisfaction either partially or simultaneously and job satisfaction affects the performance of nurses in RSUD dr. Abdulaziz.